Investigation of the Natural Pozzolans for Usage in Cement Industry. (2015) - Cobîrzan, Nicoleta; Balog, Anca-Andreea; Moşonyi, Emilia
Abstract: One of the most important aspect of selecting the proper natural pozzolanic material as admixture of Portland cement in concrete or mortars is the chemical reactivity and mineralogical content. If the chemical reactivity index and quartz content are high the pozzolans can substitute the cement from the binder groundmass in a greater proportion. The paper present mineralogical, petrographical, chemical and mechanical properties of few natural pozzolans (tuffs and perlite) in order to determine if they are proper for usage in cement industry manufacturing.